Dopplerfluxometria e avaliação morfométrica do fígado, baço, rins e grandes vasos abdominais de onças pardas (Puma concolor) da região Campo Grande, Mato Grosso do Sul, Brasil - Zulim, Rosalia Marina Infiesta [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The cougar (Puma concolor) has significant expression in the control of other vertebrates. She is at the top of the food chain, which shows its importance in their natural habitat. The species present in the official national list of animal species threatened with extinction - fish and aquatic invertebrates, the Ministry of the Brazilian Environment, published in the Normative Ruling. 3 of 27 May 2003, and updated by Ordinance N. 444 of 17 December 2014. The abdominal ultrasound examination in B, color and spectral Doppler, associated with clinical and laboratory evaluation of these animals provide values of references that will assist in the investigation of diseases, since there are no reports in the past tense respect the sonographic investigation of these cats. Ultrasound and laboratory tests were performed in fourteen animals, which eleven males and three females, free of Leishmania chagasi and from the Rehabilitation Center of Wild Animals, Campo Grande, MS, and computed the average values found for under analysis. The liver was presented hypoechoic. The wall of the gallbladder hyperechogenic, measuring 0.21 cm. The diameter of the aorta, vena cava and portal vein were respectively 1.42 cm, 1.43 cm, 0.84 cm and flowmetry gate was 32.30 cm/s. The spleen is hyperechogenic, measuring 3.25 cm in cross section. The speed of the splenic artery was 47.13 cm/s. The wall of the stomach and intestine measured 0.26 cm and 0.20 cm, respectively. The length of the left adrenal was 3.52 cm and 3.23 cm right. The thickness of the bladder wall was 0.22 cm, the right renal length 6.22 cm and 5.96 cm left. The right renal artery resistance index was 0.51 and left 0.50. Ultrasonography was efficient in the abdominal assessment brown ounces and is promising to use this tool in the clinical routine of wild animal medicine

A onça parda (Puma concolor) possui significativa expressão no controle de outros vertebrados. Ela está no topo da cadeia alimentar, o que demonstra a sua grande importância em seu habitat natural. A espécie apresenta-se na Lista nacional oficial de espécies da fauna ameaçadas de extinção - peixes e invertebrados aquáticos, do Ministério do Meio Ambiente brasileiro, publicada na Instrução Normativa n. 3, de 27 de maio de 2003, e atualizada pela Portaria n. 444, de 17 de dezembro de 2014. A análise ultrassonográfica abdominal em modo B, Doppler colorido e espectral, associada à avaliação clínico-laboratorial desses animais fornecerá valores de referências que auxiliarão na investigação de doenças, uma vez que, não existem relatos pretéritos no que tange a investigação sonográfica desses felinos. Foram realizados exames ultrassonográficos e laboratoriais em quatorze animais, sendo onze machos e três fêmeas, livres de Leishmania chagasi e provenientes do Centro de Reabilitação de Animais Silvestres, Campo Grande, MS, sendo calculadas as médias dos valores encontrados para título de análises. O fígado apresentou-se hipoecogênico. A parede da vesícula biliar hiperecogênica, medindo 0,21 cm. Os diâmetros da artéria aorta, veia cava caudal e veia portal foram respectivamente 1,42 cm, 1,43 cm, 0,84 cm e a fluxometria portal foi de 32,30 cm/s. O baço é hiperecogênico, medindo 3,25 cm em corte transversal. A velocidade da artéria esplênica foi 47,13 cm/s. A parede do estômago e intestino mediram 0,26 cm e 0,20 cm respectivamente. O comprimento da adrenal esquerda foi 3,52 cm e a direita 3,23 cm. A espessura da parede da bexiga foi de 0,22 cm, o comprimento renal direito 6,22 cm e o esquerdo 5,96 cm. O índice de resistividade da artéria renal direita foi de 0,51 e esquerda de 0,50. A ultrassonografia mostrou-se eficiente na avaliação abdominal de onças pardas e é promissora a utilização desta ...
Keywords: Abdome - Doenças; Figado - Doenças; Puma; Ultrassonografia veterinária; Vasos sanguineos; Veterinary ultrasonography